CEREMONIES IN THE SOUTHERN REGIONS OF UZBEKISTAN: THE EXAMPLE OF THE SAROY TRIBE - R.Z. Khudoyberdiyev (Western European Studies, 2025)
This article discusses the national ceremonies and customs in the southern regions of Uzbekistan. In particular, the rich cultural heritage of the nomadic people living in these areas is examined. The influence of Zoroastrianism is notably present, with the deity Mitra being revered as the protector of agriculture and livestock. Zoroastrian rituals have also had a significant impact on local customs. Additionally, the remnants of totemism can be observed, particularly the reverence for domestic animals among Turkic tribes. For example, the horse is considered a sacred animal, symbolizing prosperity and abundance. It is believed that if a horseshoe is nailed to a door, blessings will remain in the household and evil will not approach. Other customs include the hanging of sheep horns at gates, the use of talismans made from the tugdon tree, and practices such as wearing evil-eye beads and burning wild rue. These rituals demonstrate a long-standing tradition of protecting from the evil eye. National traditions are a reflection of the historical memory, cultural heritage, and spiritual values of a people. The Uzbek nation stands out for its rich lifestyle, customs, and values that have developed over centuries. In today's era of globalization, these traditions are blending with modern life, acquiring new forms and meanings
Keywords: Uzbek people; Saroy tribe; national and religious ceremonies